Anatomy for Prostatic Artery Embolization - Khunte, Mihir; Laage Gaupp, Fabian Max (Seminars in Interventional Radiology, 2025)
Prostatic artery embolization (PAE) is a minimally invasive treatment for patients with moderate to severe lower urinary tract symptoms and/or urinary retention due to benign prostatic hyperplasia (BPH), as well as hematuria secondary to prostatic bleeding. PAE achieves its therapeutic effect by inducing ischemic necrosis and reducing prostatic volume, while also decreasing neuromuscular tone. This dual mechanism addresses both the static and dynamic components of bladder outflow obstruction associated with BPH. PAE is technically challenging and necessitates in-depth knowledge of the complex and variable anatomy of the pelvic vasculature. Successful outcomes depend on precise identification of the prostatic artery and recognition of anastomoses to surrounding structures to minimize the risk of nontarget embolization and associated complications. This article reviews the prostatic arterial anatomy and explores the role of advanced imaging techniques for preprocedural planning and intraprocedural guidance to optimize procedural safety and efficacy.
Keywords: prostate artery embolization; benign prostatic hypertrophy; internal iliac artery; cone beam computed tomography; interventional radiology